ILLUSTRATIONS OF THE EARLY TREATMENT OF DEPRECIATION. - Mason, Perry (The Accounting Review, 1933)
Abstract This article discusses the basic concepts of depreciation. The fundamental facts of depreciation– the exhaustion of capital investment due to the physical or functional exhaustion of service capacity and the necessity of recovering capital investment before any profit on a venture could be claimed-have not always been understood by those individuals who regularly engaged in business undertakings. The book "The Elements of Book-keeping," by P. Kelly, published in year 1838, illustrates the inventory method of balancing the fixed asset. The 13th Annual Report of the Boston & Providence Railroad Corporation, describes a tardy recognition of accumulated depreciation, the depreciation from January 1, 1834 to December 31, 1844 being recorded in 1844. During the period, 1849-1867, a considerable amount of experimentation with methods of presenting depreciation data was evident. In the annual report of 1853, figures were inserted in the section headed "Estimated Depreciation beyond the Renewals' and deducted from surplus.